2019
DOI: 10.1080/13102818.2018.1533792
|View full text |Cite
|
Sign up to set email alerts
|

Micellar curcumin improves the antibacterial activity of the alkylphosphocholines erufosine and miltefosine against pathogenicStaphyloccocus aureusstrains

Abstract: 2019) Micellar curcumin improves the antibacterial activity of the alkylphosphocholines erufosine and miltefosine against pathogenic Staphyloccocusaureus strains, Biotechnology & Biotechnological Equipment, 33:1,[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] ABSTRACT In the light of the emerging bacterial resistance to broad-spectrum antibiotics, the search for new antibacterial therapeutics and drug combinations is one of the most challenging topics nowadays. In the present study, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…It was found that silverdecorated polymeric micelles encapsulated with curcumin exhibited strong antibacterial activity to P. aeruginosa and Staphylococcus aures (Huang et al, 2017). Similarly, Zaharieva et al reported that curcumin loaded micelles enhance the alkylphosphocholines erufosine and miltefosine antibacterial activities against pathogenic S. aureus strain (Zaharieva et al, 2019). Wang et al demonstrated that encapsulated curcumin exhibited a broad spectrum of antifungal activity by obstructing S. cerevisiae, Aspergillus niger, and Penicillium notatum.…”
Section: Antimicrobial Effectsmentioning
confidence: 99%
“…It was found that silverdecorated polymeric micelles encapsulated with curcumin exhibited strong antibacterial activity to P. aeruginosa and Staphylococcus aures (Huang et al, 2017). Similarly, Zaharieva et al reported that curcumin loaded micelles enhance the alkylphosphocholines erufosine and miltefosine antibacterial activities against pathogenic S. aureus strain (Zaharieva et al, 2019). Wang et al demonstrated that encapsulated curcumin exhibited a broad spectrum of antifungal activity by obstructing S. cerevisiae, Aspergillus niger, and Penicillium notatum.…”
Section: Antimicrobial Effectsmentioning
confidence: 99%
“…The quantitative evaluation of the inhibition effects of OrO and OrO-NP on the test microbial strains was performed using the Lambert-Pearson (LP) model considering the inhibitory effect of the applied concentration and fitting the experimental data on the base of the weighted least squares statistical method [79,80]. The program was coded in the MAPLE symbolic mathematics software.…”
Section: Mathematical Modeling Calculation Of Respiratory (Metabolic) Activitymentioning
confidence: 99%
“…The attached bacterial cells were then stained with 0.1% crystal violet for 15 min and dissolved in 96% ethanol to remove the bound dye from the stained cells. The dye bound to biofilm was re-solubilized with 150 μL of 33% acetic acid and the optical density (OD) of each well was measured at 570 nm by a microplate reader (BioTek, Germany) [ 23 ]. The following controls were included in each MBIC test plate: 1) 0.2% chlorhexidine (CHX; positive control); 2) S. mutans in medium (negative control); 3) medium only (sterility control).…”
Section: Methodsmentioning
confidence: 99%